2013
DOI: 10.2174/1567201810999131125222440
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells; Role in Tissue Repair, Drug Discovery and Immune Modulation

Abstract: Mesenchymal stromal cells (MSCs) participate in repair of damaged tissues, possess the potential to serve as a useful tool in the drug discovery field and exert immunosuppressive effects as demonstrated by their ability to modulate the immune response. Herein, the roles played by MSC differentiation and/or production of trophic factors involved in tissue repair are discussed. MSCs offer the opportunity to probe targets that conventional or differentiated cell lines do not express; thus providing a more refined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 168 publications
0
23
0
Order By: Relevance
“…Conversely, it has been proposed that MSCs mediate repair through cell education and trophic manipulation of the microenvironment [9,[32][33][34]. Given the heterogeneity of in vitro cultured MSCs, the concepts of regeneration and trophic repair may not be mutually exclusive [33,35]. In this study, MSC CM was shown to have dynamic effects pertaining to fibrotic therapy, encouraging the migration and proliferation of alveolar epithelial cells while suppressing the activation and proliferation of pulmonary fibroblasts.…”
Section: Discussionmentioning
confidence: 83%
“…Conversely, it has been proposed that MSCs mediate repair through cell education and trophic manipulation of the microenvironment [9,[32][33][34]. Given the heterogeneity of in vitro cultured MSCs, the concepts of regeneration and trophic repair may not be mutually exclusive [33,35]. In this study, MSC CM was shown to have dynamic effects pertaining to fibrotic therapy, encouraging the migration and proliferation of alveolar epithelial cells while suppressing the activation and proliferation of pulmonary fibroblasts.…”
Section: Discussionmentioning
confidence: 83%
“…MIAMI cells and other MSC populations play a critical role in endogenous tissue repair in vivo because they secrete abundant cytokines and growth factors [ 33 , 45 ]. To produce these reparative effects, MSCs must home to, or migrate towards, the site of tissue damage [ 33 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The development of antigen search methods targeting the interstitial tissue of cancer is currently in progress [28]. By targeting the stromal tissue of cancer, migration of the drug to the cancer tissue can be reduced.…”
Section: Techniques For Analyzing Cancer Stromal Tissues Of Model Animentioning
confidence: 99%